Speaking of health : assessing health communication strategies for diverse populations (Online access: NCBI NCBI Bookshelf., 2002)
"Using case studies in the areas of diabetes, mammography, and mass communication campaigns, Speaking of Health examines the ways in which messages must be adapted to the unique informational needs of their audiences if they are to have any real impact. By suggesting creative strategies and guidelines for speaking to diverse audiences now and in the future, the Institute of Medicine seeks to take health communication into the 21st century."--Jacket